Lactitol Supplementation Modulates Intestinal Microbiome in Liver Cirrhotic Patients - Lu, Haifeng; Chen, Liang; Pan, Xiaxia; Yao, Yujun; Zhang, Hua; Zhu, Xiaofei; Lou, Xiaobin; Zhu, Chunxia; Wang, Jun; Li, Lanjuan; Wu, Zhongwen (Frontiers in Medicine, 2021)
Background: Cirrhosis is a common chronic liver disease characterized by irreversible diffuse liver damage. Intestinal microbiome dysbiosis and metabolite dysfunction contribute to the development of cirrhosis. Lactitol (4-β-D-galactopyranosyl-D-glucitol) was previously reported to promote the growth of intestinal Bifidobacteria. However, the effect of lactitol on the intestinal microbiome and fecal short-chain fatty acids (SCFAs) and bile acids (BAs) and the interactions among these factors in cirrhotic patients pre- and post-lactitol treatment remain poorly understood. Methods: We profiled intestinal microbiome in liver cirrhotic patients with pre- and post-lactitol supplementation by shotgun metagenomics and targeted metabolomics methods, and compared them with healthy controls to assess the effects of lactitol supplementation on intestinal microbiome of cirrhotic patients. Results: we found that health-promoting lactic acid bacteria, including Bifidobacterium longum, Bifidobacterium pseudocatenulatum, and Lactobacillus salivarius, were increased after lactitol intervention, and significant decrease of pathogen Klebsiella pneumonia and associated antibiotic resistant genes /virulence factors. Functionally, pathways including Pseudomonas aeruginosa biofilm formation, endotoxin biosynthesis, and horizontal transfer of pathogenic genes were decreased in cirrhotic patients after 4-week lactitol intervention compared with before treatment. Conclusion: We identified lactitol-associated metagenomic changes, and provide insight into the understanding of the roles of lactitol in modulating gut microbiome in cirrhotic patients.